Dinámica familiar-escolar con adolescentes de conductas autodestructivas, casos de estudios, alumnos del Colegio Ing. José Corsino Cárdenas de la ciudad de Pasaje, en el periodo 2012-2013. - Castillo Armijos, Rocío Katherine (2014)
All research instruments used in the process, gave results that helped me to know why d each behavior, which determined that most problems stem from home, which is then added to the school, because the family as the first school and the school as second place of learning, are the basis for good personal and social development of students, which is why we recommend that you implement methods, techniques and instruments, in treating young as proposed search for a solution, it is proposed the implementation of workshops to parents and psychologists on how to work and seek means of practical solution in-school family dynamic for adolescents with self-destructive behaviors.